SOSIALISASI TIGA DOSA BESAR DALAM PENDIDIKAN UNTUK PENGUATAN PROFIL PELAJAR PANCASILA DI SMP IT LA ROYBA KOTA SERANG - Kurnaedi, Nedi; Sari, Novita; Mutaqin, Moh Fikri Tanzil; Saputra, Desma Yuliadi (LPPM Universitas Bina Bangsa, 2024)
The socialization of the Three Big Sins in education at SMP IT La Royba, Serang City is an initiative strategy aimed at strengthening the profile of Pancasila Students. This program focuses on preventing three main negative behaviors: bullying, violence, and drug propaganda, which are considered major sins in the world of education. Through this socialization, students are invited to understand the negative impacts of these three behaviors and the importance of avoiding them, with a practical emphasis on applying Pancasila values ​​such as mutual cooperation, integrity and morality in everyday life. The program involves various stakeholders, including teachers, parents, and the community, to ensure a comprehensive and inclusive approach. Socialization activities are carried out through various methods, such as seminars, group discussions and interactive activities, to ensure key messages can be received and well understood by students. The expected results of this program are the creation of a school environment that is safer, more comfortable and conducive to the learning process, as well as the formation of student characters who are more noble, disciplined and responsible. Thus, it is hoped that this socialization can support the development of a young generation of high quality and integrity, in accordance with the national education vision. This program will not only impact students, but also the entire school ecosystem, which will ultimately contribute to the creation of a better and more moral society. This entire initiative is an important step in strengthening the foundation of character education based on Pancasila values ​​in Indonesia